2017
DOI: 10.36076/2017.1.e145
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Spine Surgery: Distance Patients Will Travel for Minimally Invasive Spine Surgery

Abstract: Background: Transforaminal lumbar endoscopic discectomy is a minimally invasive spine surgery procedure performed principally for the treatment of lumbar herniated discs. Endoscopic spine surgeons around the world have noted how far patients will travel to undergo this minimally invasive spine surgery, but the actual distance patients travel has never been investigated. Objective: We present here our analysis of how far patients will travel for endoscopic spine surgery by studying the referral patterns of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…PTED is a minimally invasive full-endoscopic spine surgical procedure performed principally for the treatment of LDH. 26 It has several advantages in treating recurrent LDH, such as avoiding from the old scar tissue, decreasing operation-related complications, shortening operation time, reducing trauma, and obtaining rapid postoperative recovery. 27 The technique combines the benefits of endoscopy (direct visualization, reduced traumatization, hospital stay, and postsurgical morbidity) with optimal exposure of the intervertebral space and preservation of the dorsal musculature, the vertebrae, and the ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%
“…PTED is a minimally invasive full-endoscopic spine surgical procedure performed principally for the treatment of LDH. 26 It has several advantages in treating recurrent LDH, such as avoiding from the old scar tissue, decreasing operation-related complications, shortening operation time, reducing trauma, and obtaining rapid postoperative recovery. 27 The technique combines the benefits of endoscopy (direct visualization, reduced traumatization, hospital stay, and postsurgical morbidity) with optimal exposure of the intervertebral space and preservation of the dorsal musculature, the vertebrae, and the ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of endoscopic techniques in spine surgery has the same advantages as other forms of MISS. Respecting the surrounding tissue, avoiding blood loss, and achieving desired functional outcomes earlier are factors also seen with endoscopic surgery (11). Endoscopic spine surgery was first attempted by Kambin et al in 1988 (10).…”
Section: Arthroscopic/endoscopic Spine Surgerymentioning
confidence: 99%
“…However, it is only recently that the technique has been popularized due to the concurrent advancement in tools and imaging modalities. The use of endoscopic techniques in spine surgery has the same desirable factors as other aspects of MISS of respecting the surrounding tissue, avoiding blood loss, and earlier functional outcomes (11).…”
Section: Arthroscopic/endoscopic Spine Surgerymentioning
confidence: 99%
“…Transforaminal Endoscopic Discectomy for Central Disc Herniation Since the invention of Yeung Endoscopic Spine System (YESS) technology by Anthony Yeung in 1999, percutaneous transforaminal endoscopic disectomy has been widely used in the treatment of LDH and has achieved good results (11,12). Yeung et al (13) reported 307 cases of LDH treated with the YESS technique followed-up for more than one year, and the www.painphysicianjournal.com excellent-to-good rate was 89.3%.…”
Section: E119mentioning
confidence: 99%